Entrepreneurship : theory, process, practice - Kuratko, Donald F. (South-Western Cengage Learning, 2014)
Learn the true process of a successful entrepreneur with ENTREPRENEURSHIP: THEORY, PROCESS, PRACTICE, 9e! Presenting the most current thinking in this explosive field, this renowned entrepreneurship text provides a practical, step-by-step approach that makes learning easy. Using exercises and case presentations, you can apply your own ideas and develop useful entrepreneurial skills. Cases and examples found throughout the text present the new venture creations or corporate innovations that permeate the world economy today. This book will be your guide to understanding the entrepreneurial challenges of tomorrow.